Product design and the supply chain - Khan, Omera (Henry Stewart Talks, 2010)
Impact of product design on the supply chain, Why are today's supply chains so vulnerable?, The challenge of globalization, Competing in turbulent markets, Product life cycles are getting shorter, The risk spiral, Design influences on the responsiveness and resilience of the supply chain, Designing products for late configuration, How to reduce the transport intensity of supply chains?, The Motorola Complexity Index, Time to market, 4C's of A Design Centric Business, A Roadmap for the Design Centric Business